Galactose-alpha-1,3-galactose Specific IgE is Associated with Anaphylaxis but not Asthma. - Commins, Scott P; Kelly, Libby A; Rönmark, Eva; James, Hayley R; Pochan, Shawna L; Peters, Edward J; Lundbäck, Bo; Nganga, Lucy W; Cooper, Phil; Hoskins, Janelle M; Eapen, Saju S; Matos, Luis A; et al. (American Thoracic Society, 2012)
RATIONALE: IgE antibodies to the mammalian oligosaccharide galactose-alpha-1,3-galactose (alpha-gal) are common in the southeastern United States. These antibodies, which are induced by ectoparasitic ticks, can give rise to positive skin tests or serum assays with cat extract. OBJECTIVE: To evaluate the relationship between IgE antibodies to alpha-gal and asthma, and compare this with the relationship between asthma and IgE antibodies to Fel d 1 and other protein allergens. METHODS: Patients being investigated for recurrent anaphylaxis, angioedema, or acute urticaria underwent spirometry, exhaled nitric oxide (eNO), questionnaires, and serum IgE antibody assays. The results were compared with control subjects as well as cohorts from the Emergency Department (ED) in Virginia (n=130), northern Sweden (n=963), and rural Kenya (n=131). MEASUREMENTS AND MAIN RESULTS: Patients in Virginia with high titer IgE antibodies to alpha-gal had normal lung function, low levels of eNO, and low prevalence of asthma symptoms. Among patients in the ED and children in Kenya, there was no association between IgE antibodies to alpha-gal and asthma (odds ratios 1.04 and 0.75, respectively). In Sweden, IgE antibodies to cat were closely correlated with IgE antibodies to Fel d 1 (r=0.83), and to asthma (p<0.001). CONCLUSIONS: These results provide: i) a model of an ectoparasite-induced specific IgE response that can increase total serum IgE without creating a risk for asthma, and ii) further evidence that the main allergens that are causally related to asthma are those that are inhaled.